Bridges: United States Academia for First-Generation and International College Students - Shawn Higgins (North Broad Press, 2020)
Bridges: United States Academia for First-Generation and International College Students introduces students to a wide range of concepts, institutions, histories, and artifacts of United States college and university life. After discussing these items in easy-to-scan, concise, nuance-free prose, this textbook then offers useful lists, templates for writing and speaking in different discourses and situations, thought-provoking questions and activities for self-study and for classroom work, and pertinent hyperlinks for further information. Bridges is designed to help first-generation, first-year, English-language learners, and/or culturally unfamiliarized students more fully and successfully explore their educational environments. By using this book, students will be better prepared for the academic and social challenges of successfully undertaking higher education in English.